2019
DOI: 10.1016/j.fertnstert.2019.02.002
|View full text |Cite
|
Sign up to set email alerts
|

Infectious human papillomavirus virions in semen reduce clinical pregnancy rates in women undergoing intrauterine insemination

Abstract: Objective: To study the influence of human papillomavirus (HPV) virions present in different sperm fractions of male partners of women undergoing IUI on fertility outcome. Design: Prospective noninterventional multicenter study. Setting: Inpatient hospital fertility centers. Patient(s): Seven hundred thirty-two infertile couples undergoing 1,753 IUI cycles with capacitated sperm. Intervention(s): None. Main Outcome Measure(s): Biochemical and clinical pregnancy rate in IUI cycles with HPV-positive or HPV-negat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
39
0
2

Year Published

2020
2020
2025
2025

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(48 citation statements)
references
References 44 publications
(47 reference statements)
2
39
0
2
Order By: Relevance
“…Second, many demographic variables were not available in the database, such as body mass index, tobacco or alcohol consumption status, lifestyle factors, socioeconomic status, family medical history, fertility status, infertile male partners, and the possibility of being influenced by HPV-infected fertile male partners. Lyu et al showed that the overall prevalence of HPV DNA in semen was higher in fertility clinic attendees than in the general population [27], and Depuydt et al found that couples undergoing intrauterine insemination had a significant decrease in clinical pregnancy rate when infectious HPV virions were detected in the sperm [40]. These factors contribute to the development of infertility, and these confounders are an inherent limit of the NHIRD.…”
Section: Discussionmentioning
confidence: 99%
“…Second, many demographic variables were not available in the database, such as body mass index, tobacco or alcohol consumption status, lifestyle factors, socioeconomic status, family medical history, fertility status, infertile male partners, and the possibility of being influenced by HPV-infected fertile male partners. Lyu et al showed that the overall prevalence of HPV DNA in semen was higher in fertility clinic attendees than in the general population [27], and Depuydt et al found that couples undergoing intrauterine insemination had a significant decrease in clinical pregnancy rate when infectious HPV virions were detected in the sperm [40]. These factors contribute to the development of infertility, and these confounders are an inherent limit of the NHIRD.…”
Section: Discussionmentioning
confidence: 99%
“…And also, infected sperm is able to penetrate the oocyte, to deliver HPV genome in the oocyte and to increase the risk of pregnancy loss [2]. In vivo study, cumulative pregnancy rates after IUI and ICSI treatments showed significantly lower in HPV infected couples compared with non-infected couples, and also miscarriage rates were higher in HPV infected couples [4][5][6]. Hermonat et al [12] reported that spontaneous miscarriage products were more prevalent (60%) for HPV-DNA sequences compared to elective aborted products (20%).…”
Section: Discussionmentioning
confidence: 99%
“…Infected spermatozoa could be a vector for HPV transmission into fertilized oocytes and the infected zygote is able to perpetuate the viral genome expression at blastocyst stage and subsehttp://www.e-kmj.org Keimyung Med J quently in trophoblastic cells [3]. When semen was infected with HPV in the cycle of intrauterine insemination (IUI) or in vitro fertilization (IVF), clinical pregnancy rate was decreased [4,5]. Moreover, an increased risk of pregnancy loss and preterm delivery was reported in HPV infected male partners [4,6].…”
Section: Introductionmentioning
confidence: 99%
“…Recent reports have described a statistically significant negative effect of human papilloma virus (HPV) positivity in men and women on clinical pregnancy rates after IUI (9,10). Therefore, HPV-positive women and men should not receive IUI as a first-line treatment although it is unknown yet whether HPV positivity has an effect on IVF-ICSI pregnancy rates.…”
Section: Pro (Ivf): Couples With Unexplained Infertility Should Be Rementioning
confidence: 99%